Chromium Bioremediation Using a Combination of Two Indigenous Rhizobacteria In Vitro - Wahyu Surakusumah; Nurul Ilma Apriliani; Diah Kusumawaty; Wijanarka Wijanarka; Achmad Dinoto; Restu Utari Dewina (Al-Kauniyah: Jurnal Biologi, 2026)
Sukaregang, known for its leathercraft industry, faces chromium pollution from poorly managed tannery waste, affecting soil and water resources. The dynamic soil area influenced by plant roots, known as the rhizosphere, becomes a habitat for various microorganisms with unique metabolic capabilities that have significant potential as bioremediation agents for heavy-metal-contaminated environments. This study aims to evaluate the potential of indigenous bacterial consortia from the chromium-contaminated rhizosphere as bioremediation agents. Five bacterial genera: Pseudomonas, Citrobacter, Bacillus, Azotobacter, and Micrococcus, were identified as chromium-resistant in vitro. Compatibility tests showed that these bacterial combinations exhibited synergies without growth inhibition. Among the five consortia combinations tested (AB, BC, CD, DE, EA), consortium DE (Azotobacter and Micrococcus), exhibiting the most stable growth dynamics, characterized by a sustained stationary phase, suggesting a superior adaptive response to chromium-induced stress. Under chromium stress, the consortium EA (Micrococcus and Pseudomonas) achieved the highest chromium removal percentage at 30.78%. This study suggests that indigenous rhizobacterial consortia could be a practical approach to remediate chromium pollution in areas like Sukaregang.